Slovak Republic : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
After slowing in 2013, the Slovak economy is gathering momentum as the euro area and domestic demand recover, the latter complementing the strong export sector that has made Slovakia one of Europe's more dynamic economies. Reducing still very high unemployment remains a key challenge, as does sustaining fiscal adjustment. Manageable public and private debt as well as a sound banking system limit vulnerabilities, but Slovakia's fortunes remain closely tied to external developments, especially in the euro area, and there are risks from regional tensions since Russia provides much of Slovakia's energy and is a reasonably important export market, including for Slovakia's trading partners.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet